Cascade Downregulation of the HER Family by a Dual‐Targeted Recombinant Protein–Drug Conjugate to Inhibit Tumor Growth and Metastasis. Issue 23 (4th May 2022) - Yuan, Yang; Zhou, Sensen; Li, Cheng; Zhang, Xiaoke; Mao, Hui; Chen, Weizhi; Jiang, Xiqun
Abstract: Human epidermal growth factor receptor type 2 (HER2)‐targeted therapy can significantly improve the outcome of patients with HER2 positive cancer. However, relapse after this treatment remains a great challenge in the clinic due to tumor resistance, in which the HER network induces constitutive signal transduction. In addition, integrin receptors in the tumor extracellular matrix can mitigate the therapeutic effect of inhibitors to the growth factors receptors and tyrosine kinases. Here, the development of a recombinant protein (RP‐HI) and its drug conjugates (RPDC‐HI) to target both HER2 and integrin is reported. When simultaneously blocking HER2 and integrin by RP‐HI, functions of the HER family and their interactions with the integrin are disrupted by downregulated expressions of HER family members, leading to inhibition of several downstream signal pathways. In combination with targeted delivery of the anticancer agent, doxorubicin (DOX), RPDC‐HI significantly improves the tumor inhibition efficacy to 97.5% in treating HER2‐positive breast cancer, comparing to 34.3% for free DOX. RPDC‐HI shows even better antitumor efficiency than a monoclonal antibody, trastuzumab, when treating larger tumors. The developed dual‐targeted RPDC platform offers a new and promising strategy for treating HER2‐positive patients with synergistic therapeutic effects against tumor resistance to the conventional HER2‐targeted treatment. Abstract : Epidermal growth factor receptor type 2 (HER2) and integrin αv β3 dual‐targeted recombinant protein drug conjugate can downregulate the expressions of the HER family including EGFR (HER1), HER2, HER3, and HER4, inhibit the downstream signaling pathways, and improve the drug accumulation and distribution in tumors, leading to reduction of tumor size and significant inhibition of tumor metastasis.